Twenty four hour care in inner cities: two years' out of hours workload in east London general practice. Issue 6695 (5th August 1989) - Livingstone, A. E.; Jewell, J. A.; Robson, J.
Abstract : Two inner city general practices in east London jointly provide care outside normal working hours without using deputising services for about 14, 000 patients. The statistics on workload were reviewed for 1987 and 1988. An overall rate of face to face consultations of 4.1 per patient per year was recorded, there being 115, 965 consultations over two years for a mean list size of 14, 174 patients. Four per cent (4737) of such consultations were outside normal working hours. The annual rate of visiting outside normal hours was 128.1 per 1000 patients in 1987 (1793 visits) and 131.5 per 1000 in 1988 (1888 visits). The rates of night visiting were 18.8 (262 visits) and 18.9 (271 visits) per 1000 patients in 1987 and 1988 respectively. Only 24% of all the requests for medical help out of hours (1483/6220) were dealt with by advice given on the telephone. The high rates of consultation outside normal working hours with only a small proportion being dealt with on the telephone alone may be explained by indices of deprivation. Local rotas for out of hours work are a good compromise between meeting the needs of patients and doctors in deprived areas, but there are financial implications for inner cities.